Recognition of Sentences With Complex Syntax in Speech Babble by Adolescents With Normal Hearing or Cochlear Implants. - Nittrouer, Susan; Lowenstein, Joanna H. (Journal of Speech, Language & Hearing Research, 2023)
Purpose: General language abilities of children with cochlear implants have been thoroughly investigated, especially at young ages, but far less is known about how well they process language in real-world settings, especially in higher grades. This study addressed this gap in knowledge by examining recognition of sentences with complex syntactic structures in backgrounds of speech babble by adolescents with cochlear implants, and peers with normal hearing. Design: Two experiments were conducted. First, new materials were developed using young adults with normal hearing as the normative sample, creating a corpus of sentences with controlled, but complex syntactic structures presented in three kinds of babble that varied in voice gender and number of talkers. Second, recognition by adolescents with normal hearing or cochlear implants was examined for these new materials and for sentence materials used with these adolescents at younger ages. Analyses addressed three objectives: (1) to assess the stability of speech recognition across a multiyear age range, (2) to evaluate speech recognition of sentences with complex syntax in babble, and (3) to explore how bottom-up and top-down mechanisms account for performance under these conditions. Results: Results showed: (1) Recognition was stable across the ages of 10-14 years for both groups. (2) Adolescents with normal hearing performed similarly to young adults with normal hearing, showing effects of syntactic complexity and background babble; adolescents with cochlear implants showed poorer recognition overall, and diminished effects of both factors. (3) Top-down language and working memory primarily explained recognition for adolescents with normal hearing, but the bottom-up process of perceptual organization primarily explained recognition for adolescents with cochlear implants. Conclusions: Comprehension of language in real-world settings relies on different mechanisms for adolescents with cochlear implants than for adolescents with normal hearing. A novel finding was that perceptual organization is a critical factor.